2016
DOI: 10.1097/igc.0000000000000803
|View full text |Cite
|
Sign up to set email alerts
|

Oncologic Safety of Laparoscopy in the Surgical Treatment of Type II Endometrial Cancer

Abstract: Laparoscopy is oncologically at least not inferior to laparotomy for the surgical treatment of type II EC. Endoscopic techniques are feasible, effective, result in significantly less morbidity, and improved quality staging. Although statistical significance was not reached, laparoscopy was associated with superior oncologic results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 23 publications
2
22
0
1
Order By: Relevance
“…In addition, the prevalence of laparoscopy and improvements in surgical equipment, environment, and technology may also have increased survival after hysterectomy. Although several studies found no significant improvement in overall survival among patients with EC after laparoscopy compared with laparotomy, 18,19 some reports indicated that the morbidity of hysterectomy has decreased over recent decades. 20–22 Averette et al.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the prevalence of laparoscopy and improvements in surgical equipment, environment, and technology may also have increased survival after hysterectomy. Although several studies found no significant improvement in overall survival among patients with EC after laparoscopy compared with laparotomy, 18,19 some reports indicated that the morbidity of hysterectomy has decreased over recent decades. 20–22 Averette et al.…”
Section: Discussionmentioning
confidence: 99%
“…Il est recommandé de la réaliser par technique mini-invasive si celle-ci est techniquement possible. Même si la technicité de la laparoscopie paraît plus complexe que la laparotomie avec un risque d’exérèse ganglionnaire moindre, de nombreux articles ont validé la faisabilité et de la sûreté de la laparoscopie dans les curages: il existe moins de complications post-opératoires, la durée de séjour est plus courte et les taux de survie et de récidive sont équivalents à la laparotomie [18] , [19] , [20] , [21] , [22] , [23] . De plus, le curage lombo-aortique doit s’étendre jusqu’à la veine rénale gauche car lorsque la région lombo-aortique est atteinte, il existe un taux non négligeable de métastases au-dessus de l‘artère mésentérique inférieure (77 %) [24] , [25] .…”
Section: Discussionunclassified
“…There is a lack of data on the laparoscopic management of high-risk patients. According to our literature review, 4 recent studies have investigated laparoscopic management of patients with grade 3 and type 2 EC [14151617]. In 2012, a multicenter retrospective study, which is the first on laparoscopic management of high grade and type 2 endometrial carcinomas (n=191), concluded that high-risk histopathologic types were not a contraindication for MIS [14].…”
Section: Discussionmentioning
confidence: 99%
“…Favero et al [16] studied the feasibility, operative outcomes and oncologic safety of laparoscopic surgery in patients with type 2 EC (n=53). They concluded that LS was associated with better oncologic outcomes than LT with no statistical significance [16]. Indeed, with increasing number of patients, a statistical significance could be achieved.…”
Section: Discussionmentioning
confidence: 99%